Delayed intestinal perforation secondary to blunt force abdominal trauma in a cat. Issue 1 (April 2018) - Taylor, A; Cooper, E; Ham, K
Case summary: A 7-month-old intact male domestic shorthair cat was presented 4 h after being hit by a car. It had bilateral inguinal hernias and a mesenteric rent that were repaired surgically and a hematoma in the left retroperitoneal space. No other intra-abdominal abnormalities were identified on abdominal surgical exploration. Approximately 72 h after presentation, the cat started vomiting and developed severe abdominal discomfort. A sudden decrease in mentation and elevation of respiratory rate and effort ensued. Abdominal radiographs showed loss of detail in the abdominal cavity, and abdominocentesis confirmed septic peritonitis. The cat was euthanized, and post-mortem evaluation of the bowel revealed two 1 cm perforations of the jejunum. Relevance and novel information: To our knowledge, delayed intestinal perforation secondary to blunt force abdominal trauma has not previously been reported in cats. It has been reported in dogs, but the pathophysiology resulting in perforation is poorly understood. Delayed intestinal injury secondary to blunt force abdominal trauma has been reported in people, especially in children, as a result of motor vehicle accidents.